Effects of Euphorbia humifusa extract on growth performance and serum biomarkers in preweaned calves - Zhang, Chuntao; Xing, Zhongying; Xu, Guishan; Tu, Yan; Diao, Qiyu (Frontiers in Veterinary Science, 2025)
IntroductionThe juvenile period represents a critical rearing phase in animals, during which rearing quality directly impacts adult productive performance. Plant extracts have been used as feed additives to promote growth, inhibit bacteria, enhance immunity, improve animal health, and ensure the safety of animal products. Therefore, our study aimed to investigate the effects of Euphorbia humifusa extract (EHE) on growth performance, serum biomarkers and antioxidant mechanisms in preweaning calves.MethodsForty-eight newborn calves were randomly allocated to four groups (12 calves/group) and fed milk replacer supplemented with 0 mg (control, CON), 400 mg (Group A), 800 mg (Group B), or 1,200 mg (Group C) of EHE. Body weight and serum biomarkers were measured on d 30 and 60. Network pharmacology was employed to identify EHE-related antioxidant targets, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses.ResultsCalves in group C exhibited significantly higher average daily gain (ADG) compared with CON during d 30–60. Both dry matter intake (DMI) and ADG across treatment groups demonstrated a dose-dependent increase. Serum growth hormone (GH) shows the same trend as daily weight gain and feed intake. Serum analysis revealed that superoxide dismutase (SOD) activity in group C was significantly elevated versus CON, Network pharmacology identified 150 potential antioxidant targets of EHE, primarily enriched in pathways associated with cancer, hepatic injury, apoptosis, and viral infection, suggesting immune-modulatory effects.DiscussionBased on these findings, it can be inferred that supplementing milk replacer with EHE enhances calf growth performance, regulating oxidative stress, and it regulates signaling pathways related to immune response and apoptosis through interactions with key targets such as IL6, TP53, MAPK1, AKT1, TNF, BCL2, and ESR1.